2005
DOI: 10.1038/ng1497
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering regulatory pathways that affect hematopoietic stem cell function using 'genetical genomics'

Abstract: We combined large-scale mRNA expression analysis and gene mapping to identify genes and loci that control hematopoietic stem cell (HSC) function. We measured mRNA expression levels in purified HSCs isolated from a panel of densely genotyped recombinant inbred mouse strains. We mapped quantitative trait loci (QTLs) associated with variation in expression of thousands of transcripts. By comparing the physical transcript position with the location of the controlling QTL, we identified polymorphic cis-acting stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
288
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 354 publications
(301 citation statements)
references
References 26 publications
10
288
0
1
Order By: Relevance
“…If the expression of Kras2 was solely under the control of trans-acting factors (trans-QTL) 26,27 at different genomic locations, this would not be compatible with the model proposed. To examine these alternative possibilities, we generated an additional independent population of untreated, wild-type (FVBSPRETF1)FVB backcross mice, and measured the expression levels of Kras2 in the normal lungs of a total of 47 animals.…”
mentioning
confidence: 87%
“…If the expression of Kras2 was solely under the control of trans-acting factors (trans-QTL) 26,27 at different genomic locations, this would not be compatible with the model proposed. To examine these alternative possibilities, we generated an additional independent population of untreated, wild-type (FVBSPRETF1)FVB backcross mice, and measured the expression levels of Kras2 in the normal lungs of a total of 47 animals.…”
mentioning
confidence: 87%
“…Using this approach, a gene expression pattern strongly associated with murine obesity was identified leading to the identification of four new QTL linked to this complex phenotype. 110 More recently, genetical genomics yielded the identification of regulatory networks affecting stem cell function, 111 blood pressure, 112 and some neural phenotypes. 113 In humans, analysis of genomically controlled variation in gene expression has also been reported 114 opening a promising venue for unraveling biological pathways in complex diseases.…”
Section: Functional Genomicsmentioning
confidence: 99%
“…This approach has been called "genetical genomics" because it merges classical QTL genetics studies with whole-genome microarray analyses (Bystrykh et al, 2005;Carlborg et al, 2005;Jansen and Nap, 2001;Li et al, 2005;PerezEnciso and Misztal, 2004). We have described approaches to utilize genetical genomics approaches to nutrigenomic studies in Drosophila (Page and Ruden, 2005).…”
Section: Genetical Genomics and Nutrition Genetical Genomics And Nutrmentioning
confidence: 99%
“…In addition to pioneering studies in yeast and Arabidopsis, genetical genomics studies were also recently conducted with several isolated cell types in mice (Bystrykh et al, 2005;Carlborg et al, 2005;Jansen and Nap, 2001;Li et al, 2005;Perez-Enciso and Misztal, 2004). In yeast and Arabidopsis genetical genomics studies, it was found that the great majority of QTLs identified are "cis-QTL," which are polymorphisms in the promoter and enhancer regions that alter the expression levels.…”
Section: Genetical Genomics and Nutrition Genetical Genomics And Nutrmentioning
confidence: 99%
See 1 more Smart Citation